Implementasi Audit Pengendalian Internal untuk Meningkatkan Kinerja Keuangan dan Keberlangsungan Usaha UMKM Pabrik Citra - Mukhlisin; Salsa Amalina; Muhamad Ragis Aditya; Nabila Zaharani; Syahril Ananda Pratama (PT Pustaka Cendekia Publisher, 2025)
Micro, Small and Medium Enterprises (MSMEs) play an important role in the Indonesian economy. Based on data from the Ministry of Cooperatives and SMEs, the MSME sector contributes more than 60% tonational GDP and absorbs more than 97% of the work force. Despitethis, many MSMEs face challenges interms of good financial management and adequate internal controls. This condition hinders their ability to grow, innovate, and survive in market competition. One of the factors that cause ineffective financial managementin MSMEs is the lack of understanding and implementation of adequate internal controls. The purpose of this Community Service is to identify the obstacles faced by MSMEs in implementing effective internal controls and provide practical solutions to over come them. The method of implementation is a method that is carried out with an educational approach